La responsabilità morale delle multinazionali nel conflitto tra Russia e Ucraina - Salviato, Alessio (Filosofia Morale/Moral Philosophy, 2022)
This paper aims to investigate the moral responsibility of corporations in the conflict between Russia and Ukraine. since corporations can be considered moral agents, I argue they are responsible for offering acceptable moral reasons and for acting in accordance with moral obligations towards stakeholders. I suggest that corporations directly financing the war have a moral obligation to leave the Russian market, while those providing essential goods or services to stay. Moreover, all corporations have a duty of reparation.